Right ventricular endomyocardial fibrosis mimicking Ebstein anomaly in a patient with Behçet's disease: case report and review of the literature. Issue 3 (May 2014) - Buturak, Ali; Saygili, Ozlem; Ulus, Sıla; Kalfa, Melike; Karabulut, Hasan; Alhan, Cem; Dagdelen, Sinan; Aksu, Kenan
Abstract Behçet's disease is a multisystemic, chronic inflammatory disorder with diffuse clinical manifestations including the cardiovascular system. Endomyocardial fibrosis is a rarely seen complication of Behçet's disease leading to progressive heart failure. We report a case of right ventricular endomyocardial fibrosis mimicking Ebstein anomaly in a 26-year-old male Turkish patient with Behçet's disease, who had heart failure symptoms. In addition, the previously reported cases of endomyocardial fibrosis complicating Behçet's disease are reviewed in this article.